Analisis Implementasi ASEAN Human Rights Declaration Terkait Pelanggaran HAM Terhadap Aktivis dan Pembela HAM di Propinsi Papua dan Papua Barat Tahun 2015 - Karina Putri Indrasari (Department of International Relations, Brawijaya University, 2015)
Abstract Cases of abuses and violence in Asia, particularly in the member countries of ASEAN are still happening despite of the fact that the member countries of ASEAN has approved the ASEAN Human Rights Declaration (AHRD) and adopted it in legislation. However, in practice, the implementation of the ASEAN Human Rights Declaration is still slow in progress and receiving less special attention by both national governments member country concerned, or by the member countries of ASEAN. Unreasonable arrest and torture cases against human rights activists and defenders in Papua and West Papua, for example, are double human rights violation cases. First of all, it violates the right to speak and express the activists’ opinions. It violates their civil and political rights. Secondly, activists and human rights defenders were unreasonably arrested, and they were tortured and threatened by officers Indonesian National Police (INP) and the Indonesian National Armed Forces (INAF) during the arrest.This study examines the challenges in implementing AHRD both at national and sub-national levels by the ASEAN member countries due to ASEAN Way. Also, this research paper analyzes the challenges to implement the AHRD in Papua and West Papua Indonesia through the process associated with human rights violations suffered by human rights defenders and activists in Papua and West Papua Provinces. Then, the study presents an analysis of the violence that occurs to the human rights activists and defenders, and the de-securitization processes that hinder the implementation processes of AHRD in national and sub-national level. Then it focuses on matters what has been done by the government of Papua and West Papua in implementing this AHRD. Keywords: Human Rights; Freedom of Speech; Papua Province; West Papua Province; activists; tortured activists; ASEAN Human Rights Declaration; ASEAN Way.